2017
DOI: 10.1186/s12864-017-3953-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the differentiating ovary of the protogynous ricefield eel Monopterus albus

Abstract: BackgroundThe ricefield eel is a protogynous hermaphroditic Synbranchiform species that changes sex naturally from female to male, which offers an interesting model for studying gonadal (particularly ovarian) differentiation in vertebrates. In the present study, transcriptome sequencing of the gonad of ricefield eel larvae was performed to explore the molecular mechanisms underlying the ovarian differentiation and development.ResultsA total of 301,267,988 clean reads were generated from cDNA libraries of gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 89 publications
1
8
1
Order By: Relevance
“…Our results implyed that these genes might be associated with biological and physiological processes during gonad differentiation. Similar findings were demonstrated in bluehead wrasses (Thalassoma bifasciatum) 9 , southern bluefin tuna (Thunnus maccoyii) 10 , red porgy (Pagrus pagrus) 13 , common pandora (Pagellus erythrinus) 13 , yellow perch (Perca flavescens) 15 , and ricefield eel (Monopterus albus) 12 . Our results identified similar enriched GO terms between ovary and testis, with the highest enriched GO terms being for binding, cellular processes, and metabolic processes.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our results implyed that these genes might be associated with biological and physiological processes during gonad differentiation. Similar findings were demonstrated in bluehead wrasses (Thalassoma bifasciatum) 9 , southern bluefin tuna (Thunnus maccoyii) 10 , red porgy (Pagrus pagrus) 13 , common pandora (Pagellus erythrinus) 13 , yellow perch (Perca flavescens) 15 , and ricefield eel (Monopterus albus) 12 . Our results identified similar enriched GO terms between ovary and testis, with the highest enriched GO terms being for binding, cellular processes, and metabolic processes.…”
Section: Discussionsupporting
confidence: 70%
“…In our study, transcriptomic analysis between testis and ovary demonstrated global differential expression of transcripts during sex differentiation in juvenile snakeskin gourami. Our results showed that 9.8% (5,300) of the assembled unigenes had a significant annotation to all databases, which was considerably high when compared with previous reports of ovarian transcriptomic analysis of ricefield eel (Monopterus albus), showing only 3.36% of assembled matching to all databases 12 . Therefore, our transcriptome sequencing and annotating were considered acceptable for further analysis.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…However, because of the large genome of the A. davidianus, evolutionary analysis by comparative genome was hard to carry out. Transcriptome sequencing was a valuable way to obtain large-scale sequences without reference genome [ 21 , 22 ]. Phylogenetic analysis of transcriptome sequence data exhibited high supported tree topologies in many species [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%